Evaluation of autumn mist‐netting data for monitoring passerine populations in interior Alaska - Anna‐Marie Benson; Walter N. Johnson; Ronald P. Barry; Susan L. Guers (Wildlife Society Bulletin)
Abstract We evaluated the data from 2 autumn mist‐netting stations for monitoring passerine population trends and measuring the timing of migration. Migration‐monitoring stations were operated during autumn from 1993 to 2009 at 2 interior Alaska locations: in Fairbanks (64°50′N, 147°50′W) by the Alaska Bird Observatory (ABO) and near the Tetlin National Wildlife Refuge (NWR), Alaska, USA (63°22′N, 143°13′W) by the U.S. Fish and Wildlife Service. The location of these 2 stations, near the north and western limits of the continental landmass, provides information from the initial stages of long‐distance migration. The timing of migrant passage through ABO and Tetlin NWR were similar when all 17 years were combined. Juveniles preceded adults in 10 of 14 species at ABO and in 13 of 14 species at Tetlin NWR. Relative capture rates (log of weather‐corrected capture rates) from the ABO and Tetlin NWR stations from 1996 to 2009 were correlated for 2 of 7 species: ruby‐crowned kinglet (Regulus calendula) and yellow warbler (Dendroica petechia). A high proportion of captured birds were juveniles; therefore, these stations are most useful for monitoring an index of productivity. Power calculations indicate that for 6 of 7 species, a 50% decline in relative capture rates could be detected in a 20‐year period. These stations provide a unique contribution for monitoring passerine populations by providing a large sample of the timing of migration and productivity indices at 2 interior‐Alaska locations. Published 2012. This article is a U.S. Government work and is in the public domain in the USA.